Differences between two-way crosses and heterosis for total and live births in complete diallelic crossbreeding of five rabbit breeds - Garc?a, Yoleisy; Ponce de Le?n, Raquel; Mart?nez, Gladys S. (Cuban Journal of Agricultural Science, 2010)
The data from 4 222 kindlings between May 2003 and April 2004 were used to determine the differences between two-way crossbreeding (model A) and heterosis (model B) of total births (TB) and live births (LB) in a complete diallelic crossbreeding of five rabbit breeds (California, C; Caoba, CAO; Chinchilla, CH; New Zealand, N; and Semigiant, S). For both analyses, a linear model of fixed effects was applied through the GLM procedure considering the effects of genotype, kindling month, and kindling number. The model A was applied to ten databases, each having data from different two-way crossbreeding combinations to determine the difference between them. The model B was applied to other ten databases. Besides the two-way crossbreeding data, each one included parental purebreds for calculating the heterosis through the least square means resulting in the classic formula. According to the model A, there were significant differences of 0.75 total births and 0.82 live births between the genotypes of the two-way combination CAOCH-CHCAO. According to the model B, only the CCH-CHC crossbreeding showed positive and significant heterosis, 6.68 % for TB and 5.69 % for LB. However, for the combination CAOS-SCAO, it was also significant, but negative (-6.4 and -6.5 %). The greatest advantages, both for the heterosis and for the mean values of the traits under study, were obtained with the combinations CCH-CHC, CCAO-CAOC and CAOCH-CHCAO. Key words: rabbits, diallelic crossbreeding, heterosis, birth prolificacy.